POTENSI KANDUNGAN KIMIAWI DARI UBI JALAR UNGU (IPOMOEA BATATAS L) SEBAGAI BAHAN IDENTIFIKASI KEBERADAAN PLAK PADA PERMUKAAN GIGI - Endah Aryati Ekoningtyas; Tri Wiyatini; Fahrun Nisa (Jurnal Kesehatan Gigi, 2016)
TITLEThe potency of chemical composition of purple sweet potatoes (Ipomoea batatas L) as dental plaque identification agent on dental surfacesABSTRACTOn dental surface always been formed a transparent layer which firmly attached, known as dental plaque layer. Plaque on the tooth surface can be used as one indicator of oral hygiene. To determine the presence of plaque necessary dyes which can stain the surface of the plaque. Purple sweet potato has a natural dye that is anthocyanin. This study aims to determine the potential of the chemical content of purple sweet potato (ipomoea batatas l,) as the material identification of the presence of plaqueThis study research method was Experimental Research and Posttest Only Design as research approach. Sampling used with total Sampling methods and the number of respondents was 30 people. All respondents subjected twice treatment who gets purple sweet potato solution and hatching materials disclosing solution as a positive control at different times.Results showed  Purple sweet potato can be used as identification of the presence of plaque on the tooth surface and of the test statistic test Independent t test, obtained p 0.000 means there are differences of influence between the material of purple sweet potato with materials disclosing solution as the material identification of the presence of dental plaque. Further research is recommended in order to do the maximum staining on the surface of the plaque then seek to have the concentration of anthocyanin dyes are more concentrated. Keywords : purple sweet potato (ipomoea batatas l), identification ability, dental plaque